Chatbots from Automation to Autonomous: The Role of AI-Powered Chatbots in Driving the FinTech Next Wave of Digital Transformation - Takawira, Desmond (Global journal of Business and Integral Security, 2026)
The financial technology sector is undergoing profound digital transformation, with artificial intelligence (AI)-powered chatbots at the center of this shift. Initially designed as automation tools to manage routine tasks, chatbots have evolved into autonomous systems capable of personalized financial advice, fraud detection, and integration with core banking operations. This study examines the technical foundations underpinning this evolution and business outcomes resulting from chatbot adoption in fintech. It highlights how autonomous conversational agents transform customer engagement, enhance operational efficiency, and shape the future of digital finance business models.